The functions of microparticles in preeclampsia - Lok, C; Van Der Post, J; Sturk, A; Sargent, I; Nieuwland, R (2011)
Circulating blood cells, trophoblast cells and endothelial cells release microparticles (MP) into the maternal blood by membrane shedding. This process occurs upon activation or apoptosis of these cells. Evidence is accumulating that MP play a role in the development of thrombotic diseases. In recent years, the importance of changes in circulating MP numbers and in composition in preeclampsia has been recognized and research is now directed to discover the functional consequences of these changes. In this review we will discuss the structure and function of MP, with special emphasis on the changes in MP numbers, composition and function in pregnancy and preeclampsia. © 2010 International Society for the Study of Hypertension in Pregnancy. Published by Elsevier B.V. All rights reserved.